CARD11 gain-of-function mutation drives cell-autonomous accumulation of PD-1+ ICOShigh activated T cells, T-follicular, T-regulatory and T-follicular regulatory cells - Masle-Farquhar, Etienne; Jeelall, Yogesh; White, Jacqueline; Bier, Julia; Deenick, Elissa K.; Brink, Robert; Horikawa, Keisuke; Goodnow, Christopher Carl (Frontiers in Immunology, 2023)
Germline CARD11 gain-of-function (GOF) mutations cause B cell Expansion with NF-κB and T cell Anergy (BENTA) disease, whilst somatic GOF CARD11 mutations recur in diffuse large B cell lymphoma (DLBCL) and in up to 30% of the peripheral T cell lymphomas (PTCL) adult T cell leukemia/lymphoma (ATL), cutaneous T cell lymphoma (CTCL) and Sezary Syndrome. Despite their frequent acquisition by PTCL, the T cell-intrinsic effects of CARD11 GOF mutations are poorly understood. Here, we studied B and T lymphocytes in mice with a germline N-ethyl-N-nitrosourea (ENU)-induced Card11M365K mutation identical to a mutation identified in DLBCL and modifying a conserved region of the CARD11 coiled-coil domain recurrently mutated in DLBCL and PTCL. Our results demonstrate that CARD11.M365K is a GOF protein that increases B and T lymphocyte activation and proliferation following antigen receptor stimulation. Germline Card11M365K mutation was insufficient alone to cause B or T-lymphoma, but increased accumulation of germinal center (GC) B cells in unimmunized and immunized mice. Card11M365K mutation caused cell-intrinsic over-accumulation of activated T cells, T regulatory (TREG), T follicular (TFH) and T follicular regulatory (TFR) cells expressing increased levels of ICOS, CTLA-4 and PD-1 checkpoint molecules. Our results reveal CARD11 as an important, cell-autonomous positive regulator of TFH, TREG and TFR cells. They highlight T cell-intrinsic effects of a GOF mutation in the CARD11 gene, which is recurrently mutated in T cell malignancies that are often aggressive and associated with variable clinical outcomes.